Prevalencia de parásitos gastroentéricos con riesgo zoonótico en caninos (canis familiaris) en zonas urbanas del cantón Riobamba. - Escudero Pozo, Jorge Luis (2021)
The purpose of this research was to determine the Prevalence of Canine Zoonotic Gastrointestinal Parasites (Canis familiaris) in public parks and recreation spaces in the Riobamba canton. It is possible to determine the zoonosis of key gastrointestinal parasites in the inhabitants of areas surrounding public parks and recreation spaces investigated in Riobamba city. Besides, is characterized by the zoonotic gastrointestinal parasite population presented in dogs with respect to the population surrounding them. the parks and recreational spaces investigated. The methodological approach to carry out this study is based on a correlational cross-sectional experimental design. Investigations of a documentary, field, quantitative, qualitative type are declared. Scientific methods of analysis and synthesis of information sources, case study method, analytical empirical method, expert method, inductive deductive method and experimental analysis method are adopted. The study of the sample size of 200 dogs in public spaces and open parks in the city of Riobamba, shows protozoan parasites (97, 49%), Cryptosporidium parvum (19, 10%); Entamoeba histolytic (8.4%); Isospora canis (8.4%); Giardia Lamblia (60, 30%). Regarding the presence of Helminths (93, 47%), Ancylostomas sp (16, 8%); Mesostephanus sp (12.6%); Toxocara canis (18.9%); Echinococcus granulosus (27.14%); Apophallus donicus (5.3%); Trichuris vulpis (7.4%); Hookworm stenocephala (8.4%); and negative dogs in the analyzes, only (10, 4%). Regarding the presence and prevalence of parasites in neighbors near parks and public spaces open to recreation, clinical analyzes in children (26) indicate the presence of Giardia lamblia, Entamoeba Hystolitica. The research is socialized to the public actors of health and animal sanitary control, as a basis for making decisions and strategies for the preservation of health in the inhabitants of the city. It is suggested to replicate this research in other key urban areas, bearing in mind that socio-environmental conditions differ according to context. Thus, there may be other manifestations of parasitism and the prevalence of Canine Zoonotic Gastrointestinal Parasites (Canis familiaris) in different Socioenvironmental contexts, in the city of Riobamba.